Mikroekonometria finansowa : zarys problematyki - Gruszczyński, Marek (Financial microeconometrics : scope and outline, 2006)
Financial microeconometrics covers the subjects of application of econometric techniques to financial microdata. In a sense, it is a part of financial econometrics, although typically this latter one mostly concentrates on time series. Financial microeconometrics includes such topics as: credit risk forecasting models, bankruptcy prediction models, event studies on capital markets, market microstructure models, models for predicting mergers and acquisitions etc. Paper describes main features of financial microeconometrics, as well as its scope. The dilemmas linked with the adequate application of econometric techniques are shown along with the presentation of majors streams of financial microeconometrics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 111-118